The impact of perceived usefulness, perceived ease of use, and trust towards technology adoption: A case study on On-Demand deals Corporation, a pioneer in the Philippine cloud convenience industry - Alunan, Joseph Ken G. (Animo Repository, 2022)
The purpose of this study is to investigate the impact of perceived usefulness, perceived ease of use, and trust towards technology adoption of On-Demand Deals consumers using the Technology Acceptance Model (TAM) which served as the foundation for this study. A total of nine questions were used as a guide which made the researchers use different methods such as descriptive statistics, Spearman’s Rank-Order correlation, regression analysis, multicollinearity test (VIF), Durbin-Watson test, and kurtosis & skewness normality test to determine the results of this study. The researchers discussed the background of each variable in the review of related literature. An online survey was conducted where a total of 162 respondents completed the survey. The results revealed that the three independent variables, namely perceived usefulness, perceived ease of use, and trust have a high-positive correlation. Additionally, the results showed that the three independent variables have a significant impact towards technology adoption. The results also showed a severely high VIF but upon further investigation revealed that the high amount of multicollinearity, it is, “statistically significant in the face of that collinearity.” Despite this, the researchers were able to come up with possible recommendations based on the results of this study that would be beneficial for the company.